The use of using social networking sites in teaching and learning among educators and learners - Adnan, Wardatul Hayat; Bahar, Nurhidayah (Inderscience, 2019)
This study aims to explore how learners and educators use social networking sites (SNSs) for education-related activities and identify the factors that influence their usage. The study was conducted at a private institute for higher learning (IHL) in central Malaysia involving learners at different levels of study and educators from various positions. A total of 200 respondents consisting of 100 learners and 100 educators participated in the self-administered questionnaire. Chi-square and regression analyses were used to determine the significance of demographic factors (education and gender) and other factors such as perceived privacy (PP), perceived security (PS), perceived trust (PT), web experience (WE), computer anxiety (CA), social norms (SN), enjoyment (ET), desire to give information (GV) and desire to get information (GT) towards their intention to use SNSs. The findings illustrate that other than external factors, demographic factors also influence the use of SNSs for both learners and educators. Copyright © 2019 Inderscience Enterprises Ltd.